The medial tibial stress syndrome score: item generation for a new patient reported outcome measure - Winters, M (South African Journal of Sports Medicine, 2016)
Ba ckground: There is no valid and reliable instrument that evaluates injury severity and treatment effects for medial tibial stress syndrome (MTSS) patients. Objective: The aim was to generate items for the MTSS score, a new patient-reported outcome measure for patients with MTSS. Methods: The authors consulted experts in the field of MTSS to generate items that measure the severity of MTSS and to reach consensus on the relevance of items for the MTSS score. This research consisted of a pilot study and two Delphi rounds. The Delphi approach entails the consultation of experts about a topic for which no evidence is available during which consensus is sought on this topic. Additionally, 20 MTSS patients appraised the MTSS score on readability and comprehension. Results: Nineteen experts consented to participate, 13 of whom reached consensus. Generated items address the following domains: ‘limitation in sporting activities’, ‘pain while performing sporting activities’, ‘pain while performing activities of daily living’ and ‘pain at rest’. Patients with MTSS confirmed the good readability and comprehension of the items. Conclusion: This study supports the importance of items in the aforementioned domains while evaluating treatment effects in patients with MTSS.